The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1186/s12931-018-0969-7
|View full text |Cite
|
Sign up to set email alerts
|

Gasometric gradients between blood obtained from the pulmonary artery wedge and pulmonary artery positions in pulmonary arterial hypertension

Abstract: IntroductionLittle is known on the pulmonary gradients of oxyhemoglobin, carboxyhemoglobin and methemoglobin in pulmonary arterial hypertension (PAH). We sought to determine these gradients in group 1 PAH and assess their association with disease severity and survival.MethodsDuring right heart catheterization (RHC) we obtained blood from pulmonary artery (PA) and pulmonary artery wedge (PAW) positions and used co-oximetry to test their gasometric differences.ResultsWe included a total of 130 patients, 65 had g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 47 publications
(46 reference statements)
0
2
0
Order By: Relevance
“… PAWP determination: We routinely seek to obtain blood from the distal port of the pulmonary artery catheter while in the wedge position. A blood oxygenation >90% ( 5 ) supports the PAWP determination ( 6 ). When we questioned the validity of the PAWP measurement, we reduced the amount of air in the pulmonary artery balloon or advanced the pulmonary artery catheter to a different branch or the contralateral pulmonary artery ( 5 ).…”
mentioning
confidence: 67%
“… PAWP determination: We routinely seek to obtain blood from the distal port of the pulmonary artery catheter while in the wedge position. A blood oxygenation >90% ( 5 ) supports the PAWP determination ( 6 ). When we questioned the validity of the PAWP measurement, we reduced the amount of air in the pulmonary artery balloon or advanced the pulmonary artery catheter to a different branch or the contralateral pulmonary artery ( 5 ).…”
mentioning
confidence: 67%
“…Therefore, other pathophysiological explanations should be considered, which may be supported by our results. An analysis of postcapillary blood gases in a small retrospective study showed that patients with PAH had significantly lower PaCO 2 values in blood gases derived from the pulmonary artery than patients with PH in Groups 2-5, and this difference becomes much more pronounced in postcapillary gases (i.e., with more pulmonary passage of blood) [25]. This implies that hypocapnia is a very consistent feature of PH Group 1 (PAH) and could have other explanations, perhaps due to specific features and pathophysiological changes in the pulmonary artery that play a central role in PAH, such as endothelial dysfunction.…”
Section: Discussionmentioning
confidence: 99%